Treatment of allergic rhinitis using mobile technology with real‐world data: The MASK observational pilot study. Issue 9 (22nd March 2018) - Bousquet, J.; Devillier, P.; Arnavielhe, S.; Bedbrook, A.; Alexis‐Alexandre, G.; van Eerd, M.; Murray, R.; Canonica, G. W.; Illario, M.; Menditto, E.; Passalacqua, G.; Stellato, C.; et al.
Abstract: Background: Large observational implementation studies are needed to triangulate the findings from randomized control trials as they reflect "real‐world" everyday practice. In a pilot study, we attempted to provide additional and complementary insights on the real‐life treatment of allergic rhinitis (AR) using mobile technology. Methods: A mobile phone app ( Allergy Diary, freely available in Google Play and Apple App stores) collects the data of daily visual analog scales (VAS) for (i) overall allergic symptoms, (ii) nasal, ocular, and asthma symptoms, (iii) work, as well as (iv) medication use using a treatment scroll list including all medications (prescribed and over the counter (OTC)) for rhinitis customized for 15 countries. Results: A total of 2871 users filled in 17 091 days of VAS in 2015 and 2016. Medications were reported for 9634 days. The assessment of days appeared to be more informative than the course of the treatment as, in real life, patients do not necessarily use treatment on a daily basis; rather, they appear to increase treatment use with the loss of symptom control. The Allergy Diary allowed differentiation between treatments within or between classes (intranasal corticosteroid use containing medications and oral H1‐antihistamines). The control of days differed between no [best control], single, or multiple treatments (worst control). Conclusions: This study confirms the usefulness of the Allergy Diary in accessing and assessing everyday use and practice in AR. This pilot observational study uses a very simple assessment (VAS) on a mobile phone, shows novel findings, and generates new hypotheses.